Study Komparatif: Perlindungan Hukum pada Perempuan Korban Kekerasan Dalam Rumah Tangga Di Indonesia - Evi Yanti; Heni Susanti (UIR Law Review, 2023)
The aim of the first writing is to find out what the regulations regarding domestic violence are in Indonesia. Second, to find out what the legal protection regulations are for victims of domestic violence in Malaysia. The method in this research is normative legal research. Normative legal research is a type of legal research obtained from literature study, by analyzing a legal problem through statutory regulations, literature and other reference materials. Examining criminal acts of domestic violence in Indonesian criminal law, namely Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and in Malaysian criminal law, namely the 1994 Domestic Violence Act (Deed 521) and the Malaysian Violence Code. Results of This research is that legal protection for wives who are victims of domestic violence according to this law is (1) temporary protection. Temporary protection is protection that is directly provided by the police and/or social institutions or other parties, before the issuance of a protection order from the court. (2) Imposition of a protective order by the court; (3) Providing a Special Service Room at the police station; (4) providing a safe house or alternative residence; (5) providing legal consultations by advocates to victims at the level of investigation, prosecution and examination at court hearings. Legal protection for wives of victims of domestic violence in Malaysia is based on the Management and protection of victims of domestic violence is based on the 1994 Domestic Violence Act (1994).